Do academic courses relate to entrepreneurship influence career choices in the Democratic Republic of the Congo. - Christian Mwemezi Ngangura; Mumbere E. Lubula; Jocelyne Ntwali Murhonyi; Justice Mensah (African Scientific Journal, 2024)
Abstract This research examines the impact of entrepreneurship training courses on employees' willingness to become entrepreneurs and the time required to implement a business idea in the context of the Democratic Republic of Congo. The study analyzes survey data from 2005 and 2012, utilizing Heckman's selection model for econometric estimation. The results indicate that entrepreneurship training not only motivates employees to pursue entrepreneurial endeavors but also reduces the time needed to bring their business ideas to fruition. These findings are consistent with the 2012 data, reinforcing the link between entrepreneurship training and broader reforms aimed at enhancing the business environment. Keywords: willingness to undertake, training courses related to entrepreneurship, Heckman model